Intervention program: together against gender violence - Cárdenas Avalos, Sara Grimilda (2021)
This article proposes an intervention program to create consciousness among elementary school students and parents of Basic and Regular Education about gender violence to eventually identify gender’s violence ways of expression and the different aspects where these develop such as their homes, school, and society in general. Given that these attitudes tend to be blinded or normalized when a type of violence is manifested oriented by the gender. Accomplishing this, it will promote a better coexistence generating better opportunities for everyone. In addition, it will allow to strengthen the integral development of students, who not only will be able to identify these types of situations, but will also take a stand and act upon it, thus, becoming an example for their surroundings. From This educational intervention perspective, it puts educators as mobile agents to counter these sexist practices that start rooting from childhood, thus, a new generation will be  formed with directed values based on gender equality.